2008
DOI: 10.1002/cbdv.200890085
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Asymmetric Catalysis in Fragrance Chemistry

Abstract: Opposite enantiomers of a chiral fragrance may exhibit different olfactory activities making a synthesis in high enantiomeric purity commercially and scientifically interesting. Accordingly, the asymmetric synthesis of four chiral odorants, Fixolide, Phenoxanol, Citralis, and Citralis Nitrile, has been investigated with the aim to develop practically feasible processes. In the devised synthetic schemes, the key step that leads to the formation of the stereogenic center is the homogeneous asymmetric hydrogenati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…In fact, the asymmetric conjugate addition of dimethylzinc to unsaturated compounds can be a very direct method to obtain a methyl‐substituted stereogenic center, a structural motif that often plays an important role in determining the biological activity of numerous natural compounds. In particular, we focused our attention on the development of new synthetic approaches for the preparation in optically active form of some valuable fragrances such as 3‐methyl‐5‐phenyl‐pentanol (Phenoxanol) and the structurally related fragrances 3‐methyl‐5‐phenyl‐pentanaldehyde (Citralis) and 3‐methyl‐5‐phenyl‐pentanenitrile (Nitrile Citralis)13, 14 (Scheme ), choosing 3‐phenylpropylidenmalonate ( 5 ) as starting substrate on which to test the asymmetric addition.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the asymmetric conjugate addition of dimethylzinc to unsaturated compounds can be a very direct method to obtain a methyl‐substituted stereogenic center, a structural motif that often plays an important role in determining the biological activity of numerous natural compounds. In particular, we focused our attention on the development of new synthetic approaches for the preparation in optically active form of some valuable fragrances such as 3‐methyl‐5‐phenyl‐pentanol (Phenoxanol) and the structurally related fragrances 3‐methyl‐5‐phenyl‐pentanaldehyde (Citralis) and 3‐methyl‐5‐phenyl‐pentanenitrile (Nitrile Citralis)13, 14 (Scheme ), choosing 3‐phenylpropylidenmalonate ( 5 ) as starting substrate on which to test the asymmetric addition.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, they synthesized both enantiomers of a new odorant 1 on the basis of the structure of Cashmeran, a polycyclic musk, and found that the ( R )‐enantiomer ( R )‐ 1 displayed a typical woody–musky Cashmeran odour, and the ( S )‐enantiomer ( S )‐ 1 had no musk odour (Figure ) . Enantiomers of many chemical compounds are perceived differently as odorants . Only ( R )‐ 1 was similar in odour profiles to Cashmeran in spite of the structure of 1 being different from that of Cashmeran.…”
Section: Introductionmentioning
confidence: 99%
“…It is now well recognized that human nose may perceive in a different way the enantiomers of a chiral odorant; in other words, the olfactory notes of two enantiomers may be different both in quality and in intensity 1–6. This phenomenon is not only of great scientific interest, but also of primary practical importance for at least three main reasons: (i) in perfumery there is an increasing demand for odorants to create new unique olfactive notes; (ii) there are environmental and safety concerns arising from the increasing use of odorants and their interaction with the ecosystem and human beings; and (iii) the synthesis of single enantiomer is patentable 7…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal asymmetric catalysis is among the most powerful tools suitable for the synthesis of enantiomerically enriched substances on practical scale14 and our research group has been for years involved in the application of homogeneous asymmetric catalysis7 to the synthesis of enantiomerically enriched fragrances such as Galaxolide®,15 Florydral®,16, 17 Citralis Nitrile®,18 and Phenoxanol® 19. We wish to report here a new approach to the enantioselective synthesis of ( R )‐ and ( S )‐Rosaphen based on the catalytic asymmetric hydrogenation of 2‐methyl‐5‐phenylpent‐2‐enoic acid.…”
Section: Introductionmentioning
confidence: 99%